Manifestasi Pengorbanan Komunitas Redkar Kota Probolinggo - Alfiana Tri Octavira; Elly Suhartini; Jati Arifiyanti (Institut Nalanda, 2023)
Probolinggo City is the fourth-largest city in East Java. In 2021, the population of Probolinggo City was 241,202. The management of natural disasters, especially fire disasters, must be carried out in Probolinggo City using the right principles and methods. In addition to paid firefighters, there are also volunteer firefighters (Redkar). Redkar is a resident of Probolinggo City, especially the youths who participate in the firefighting unit in Probolinggo City. This study aims to determine and analyze the description of the altruistic behavior of Redkar Probolinggo City. The altruistic behavior of the Redkar community in dealing with natural disasters was studied using the altruistic concept of suicide and the perspective of Emile Durkheim's theory of social solidarity. The research was conducted using a qualitative method with a phenomenological approach. Data was collected through observation, interviews, and documentation. The results showed that Redkar had a sense of solidarity. Altruistic Redkar has solidarity that leads to organic solidarity, as explained by Emile Durkheim, namely that which is built on the basis of differences and persists in those differences in the fact that everyone has different jobs and responsibilities. Thus, the division of labor here forms an orderly division of labor, and solidarity arises because of differences and a sense of mutual need.